2018
DOI: 10.1021/acs.cgd.7b01523
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemical Assembly of Nalidixic Acid Bioinspired Metal–Organic Compounds and Complexes toward Improved Solubility

Abstract: Nalidixic acid is an antibiotic from the quinolones family whose bioavailability is limited due to its low solubility. The development of complexes and bioinspired metal−organic frameworks has been explored as a way to achieve controlled drug delivery and release, and we demonstrate that they can also be used to tune drugs' physicochemical properties, such as solubility. Herein we disclose a series of complexes and frameworks of nalidixic acid and Zn. One of these frameworks duplicates the solubility of nalidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 71 publications
1
19
0
Order By: Relevance
“…Meanwhile, quite a few APIs could also serve as good candidates for constructing new complexes and further enrich the coordination chemistry and biochemistry [6]. To date, a variety of metal complexes were constructed from API-based organic ligands, such as norfloxacin [7], enoxacin [8], ofloxacin [9], letrozole [10], fluconazole [11], and nalidixic acid [12]. The resulting complexes may exhibit more enhanced biological properties in comparison with the pure API molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, quite a few APIs could also serve as good candidates for constructing new complexes and further enrich the coordination chemistry and biochemistry [6]. To date, a variety of metal complexes were constructed from API-based organic ligands, such as norfloxacin [7], enoxacin [8], ofloxacin [9], letrozole [10], fluconazole [11], and nalidixic acid [12]. The resulting complexes may exhibit more enhanced biological properties in comparison with the pure API molecules.…”
Section: Introductionmentioning
confidence: 99%
“…MOFs with biocompatible composition were reported to be viable drug carriers to overcome some of the problems related to drug delivery [ 9 , 20 , 21 , 22 ]. In particular, MOFs designed using antibiotics as ligands to yield antibiotic coordination frameworks (ACFs) were proposed to improve the antimicrobial activity [ 23 , 24 , 25 ], as well as the physicochemical properties of the antibiotics [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…The coordination of quinolones to biocompatible metals is of considerable interest from biological and pharmaceutical point of views and it has been shown to be an alternative approach to obtain compounds with improved antimicrobial activity while simultaneously altering their physicochemical characteristics [18,19]. Our group has proven that bio-inspired metal-organic frameworks of nalidixic acid, the first quinolone antibiotic, have increased solubility and bioactivity compared to the free antibiotic [20,21]. Efthimiadou et al studied the antimicrobial activity of several pipemidic acid complexes, as well as their interaction with calf-thymus (CT) DNA with diverse spectroscopic techniques, and showed that the complexes are able to bind to DNA; in all the complexes, a B → A CT DNA transition is detected [22].…”
Section: Introductionmentioning
confidence: 99%